Effect of sodium fluoride on growth and yield in wheat (Triticum aestivum) - SINGH, JOLLY; SINGH, DEVRAJ; CHAUHAN, S V S (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1998-99 and 1999-2000 on the effect of various concentrations (25,50, 1000 and 2000 ppm) of sodium fluoride on growth and yield in ’HD 2329’ wheat (Triticum aestivum L. emend Fiori and Paol). Different concentrations of sodium fluoride inhibited germination, plant height, leaf size, number of effective tillers/plant, ear length, number of flowers/ear, number of seeds/plant, 100-grain weight, total yield/plant. The leaves of plants grown in soil with higher concentrations of sodium fluoride exhibited chlorosis and necrosis. The sodium fluoride treated plants also showed significant reduction in ear length, number of flowers/ear, 100-seed weight and total yield.